ANALISIS MODEL VECTOR AUTO REGRESSION (VAR) TERHADAP HUBUNGAN ANTARA PERTUMBUHAN EKONOMI DENGAN PENANAMAN MODAL ASING (PMA) DI INDONESIA - Suhel Suhel (Department of Development Economics, Universitas Sriwijaya, 2008)
This Research interrelationship analysis between economic growth and capital investment foreign (PMA) in Indonesia by using Vektor Auto Regression (VAR). Analysis VAR is good enough analyzer in the case of forecasting. If two variables are anticipated have interrelationship, then in estimate making for first variable must consider second variable behavior, conversely. From research that conducted find that interrelationship between Capital investment foreign (PMA) with Economic growth (PDB) in range of time 1990 pin-cushions 2006 unprovable. Relation/link that happening is unidirectional that is PMA influences Economic growth (PDB) No the happening of interrelationship is referred [as] statistically also can give other indication, that is that economic growth are more determined by other factors, outside Capital investment Asing. If seen data series PDB according to usage, economic growth Indonesia are more predominated by consumption, not by investment Must existence of continuation research by join capital investment variable, that consisted of PMA and PMDN. For government, efectivity of withdrawal policy PMA must continuity, remember persangan PMA inter-states growing tightens. Key Words: Economic growth, Capital investment foreign.